The Right to Truth in Transitional Justice - Hassan, Nouran (AUC Knowledge Fountain, 2025)
Transitional justice is sought by nations suffering from legacies of human rights violations. The field of transitional justice stands on four main pillars: truth seeking, criminal justice, reparations and guarantees of non-recurrence. It promotes utilizing legal and non-legal mechanisms to achieve a transition to democracy and the mechanisms employed must relate to, at least, one of its pillars. Truth is considered substantial for transitions to happen. Revealing the truth is believed to be essential for reconciliation and promoting peace. However, in various experiences the truth did not lead to reconciliation and was widely distorted. The approach of the transitional justice framework to truth is quite limited. It neglects the intrinsic nature of truth as a subjective product of power. Also, the transitional justice framework associates truth-seeking with the notion of the right to truth which happens to be legally vague and suffers from various gaps in its jurisprudence. Hence, the efforts of truth-seeking do not lead to the outcomes associated with it. In fact, the approach of transitional justice to truth is exclusive and opens the door for it to be manipulated by political powers to solidify their control over the people. This research deconstructs the notion of truth in transitional justice and analyzes the framework’s approach to truth. it deconstructs the notion of truth on different levels: legal, political and philosophical and criticizes the limitedness of the approach of transitional justice to truth.